Capital Structure Decisions: Evidence from Singapore - Chang, Xin Yu (2015)
This dissertation examines the determinants of capital structure in Singapore listed companies. Most prior empirical studies investigate the determinants of capital structure in developed countries, particularly in the United States and Europe, with only a few examining this topic in Asia Pacific. This dissertation focuses on Singapore to find out the factors that affect Singapore listed companies’ capital structure decision. The dissertation uses panel data from the Worldscope database which includes 561 listed companies in Singapore over 10 ten years from 2005 to 2014. This dissertation will first discuss the theories of capital structure, the Modigliani and Miller theorem, trade-off theory and pecking order theory. From these come the most important factors affecting capital structure decisions. The determinants of capital structure considered in this dissertation are profitability, liquidity, non-debt tax shields, firm size, growth opportunity, tangibility and industry classification. Three leverage measurements are used, which are short term debt ratio (STA), long term debt ratio (LTA) and ratio of total debt over total assets (TDA). The data are estimated by using a fixed effect model as it is the most appropriate model for the sample data. This is evidenced by using Breusch-Pagan Lagrange multiplier (LM) tests and Hausman tests. The findings indicate a significant impact of profitability, liquidity, non-debt tax shields, firm size, and industry classification on the borrowing decision for Singapore listed companies. However, the findings show growth opportunity and tangibility have insignificant impact on Singapore listed companies’ capital structures. Besides that, profitability is found to be significant negatively to leverage, no matter which leverage measurement is used. The findings are mixed, with some evidence that Singapore listed companies seem not to be following any capital structure theories.